2006
DOI: 10.2223/jped.1460
|View full text |Cite
|
Sign up to set email alerts
|

Response to polysaccharide antigens in patients with ataxia-telangiectasia

Abstract: Fonte financiadora: FAPESP.Artigo submetido em 26.08.05, aceito em 09.11.05. AbstractObjective: To analyze the production of antibodies to polysaccharide antigens in patients with ataxia-telangiectasia. Patients and methods:We used the ELISA technique to measure the levels of IgG antibodies to serotypes 1, 3, 5, 6B, 9V and 14 of Streptococcus pneumoniae in 14 patients with ataxia-telangiectasia before and after immunization with 23-valent polysaccharide vaccine. Adequate response to individual polysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…76 Immunizations Most patients will have already received live viral vaccines (like measles, mumps, rubella [MMR] or varicella-zoster virus [VZV] vaccines) without complications before being diagnosed with ataxia-telangiectasia. [85][86][87] Expert guidelines recommend vaccination of all patients with ataxia-telangiectasia with 13-valent pneumococcal conjugate vaccine followed by 23-valent pneumococcal polysaccharide vaccine, repeated every 5 years. 76 Live oral polio vaccine should not be administered.…”
Section: Antibioticsmentioning
confidence: 99%
“…76 Immunizations Most patients will have already received live viral vaccines (like measles, mumps, rubella [MMR] or varicella-zoster virus [VZV] vaccines) without complications before being diagnosed with ataxia-telangiectasia. [85][86][87] Expert guidelines recommend vaccination of all patients with ataxia-telangiectasia with 13-valent pneumococcal conjugate vaccine followed by 23-valent pneumococcal polysaccharide vaccine, repeated every 5 years. 76 Live oral polio vaccine should not be administered.…”
Section: Antibioticsmentioning
confidence: 99%
“…People with A-T often have a suboptimal response to the 23-valent pneumococcal polysaccharide vaccine (34), as well as to other vaccines. Limited data suggest that the response to the 7-valent pneumococcal conjugate vaccine may be more robust (74).…”
Section: General Care Issuesmentioning
confidence: 99%
“…33,34 In both patients with Wiskott-Aldrich syndrome (WAS) and those with ataxia telangiectasia (AT), several small studies have reported poor responses to polysaccharide vaccines in the majority of patients. 35,36 A small study in patients with AT demonstrated that initial vaccination with PCV and subsequent vaccination with PPV could lead to higher antibody levels to PCV-specific serotypes and non-PCV serotypes. 37 The titers were determined by using ELISA with a PPV mix as the antigen.…”
mentioning
confidence: 99%